An overview of SARS-COV-2 epidemiology, mutant variants, vaccines, and management strategies. Issue 10 (October 2021) - Farooqi, Tahmeena; Malik, Jonaid Ahmad; Mulla, Almas Hanif; Al Hagbani, Turki; Almansour, Khaled; Ubaid, Mohammed Abrar; Alghamdi, Saleh; Anwar, Sirajudheen
Abstract: Background: Over the last two decades, humanity has observed the extraordinary anomaly caused by novel, weird coronavirus strains, such as severe acute respiratory syndrome (SARS) and Middle East respiratory syndrome (MERS). As the severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) virus has made its entry into the world, it has dramatically affected life in every domain by continuously producing new variants. The vaccine development is an ongoing process, although some vaccines got marketed. The big challenge is now whether the vaccine candidates can provide long-lasting protection or prevention against mutant variants. Methods: The information was gathered from various journals, electronic searches via Internet-based information such as PubMed, Google Scholar, Science Direct, online electronic journals, WHO landscape, world meters, WHO website, and News. Results: This review will present and discuss some coronavirus disease 19 (COVID-19) related aspects including: the pathophysiology, epidemiology, mutant variants vaccine candidates, vaccine efficacy, and management strategies. Due to the high death rate, continuous spread, an inadequate workforce, lack of required therapeutics, and incomplete understanding of the viral strain, it becomes crucial to build the knowledge of its biological characteristics and make available the rapid diagnostic and vital therapeutic machinery for the combat and management of an infection. Conclusion: The data summarizes current research on the COVID 19 infection and therapeutic interventions, which will direct future decision-making on the effort-worthy phases of the COVID 19 and the development of critical therapeutics. The only possible solution is the vaccine development targeting against all variant strains to halt its progress; the identified theoretical and practical knowledge can eliminate the gaps to improve a better understanding of the novel coronavirus structure and its design of a vaccine. In addition, to that the long-lasting protection is another challenging objective that need to be looked into.